2014
DOI: 10.2118/166478-pa
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cosolvents To Improve Alkaline/Polymer Flooding

Abstract: We have found that the addition of low concentrations of certain inexpensive light cosolvents to alkaline/polymer (AP) solutions dramatically improves the performance of AP corefloods in two important ways. First, the addition of cosolvent promotes the formation of low-viscosity microemulsions rather than viscous macroemulsions. Second, these light cosolvents greatly improve the phase behavior in a way that can be tailored to a particular oil, temperature, and salinity. This new chemical enhanced-oil-recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…It has been found that the addition of low concentrations of certain inexpensive light cosolvents to AP solutions dramatically improves the performance of AP corefloods in two important ways [86]:…”
Section: Use Of Cosolventsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the addition of low concentrations of certain inexpensive light cosolvents to AP solutions dramatically improves the performance of AP corefloods in two important ways [86]:…”
Section: Use Of Cosolventsmentioning
confidence: 99%
“…Twelve successful ACP corefloods using four different crude oils ranging from 12 • to 24 • API have been reported in detail [86]. The ACP process shows special promise for heavy oils, which tend to have large fractions of soap-forming acidic components, but is applicable across a wide range of oil gravity.…”
Section: Use Of Cosolventsmentioning
confidence: 99%
“…Even though co-solvents improve aqueous stability, facilitate faster equilibration of the microemulsion phase, lower the microemulsion viscosity, mitigate the formation of ordered/condensed structures and broaden the low IFT salinity window, among other benefits (Salter, 1977;Abe et al, 1986;Sanz and Pope, 1995;Levitt et al, 2009;Frank et al, 2007;Sahni et al, 2010;Fortenberry et al, 2015), they also tend to increase the IFT. Developing chemistries with dual characteristics of a surfactant and a co-solvent could avoid or minimize this disadvantage.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially beneficial for EOR when the macroemulsions, gels, or liquid crystals have a high viscosity. Co-solvents play a pivotal role in providing favorable microemulsion rheology (Walker et al, 2012;Fortenberry et al, 2015;Tagavifar, 2014). Co-solvents reduce the bending modulus (increasing the fluidity) of the interface which facilitates low microemulsion viscosity and Newtonian behavior (de Gennes and Taupin, 1982; Safinya…”
Section: Introductionmentioning
confidence: 99%
“…et al, 1989; Strey and Jonströmer, 1992;Wennerström and Olsson, 2014). Co-solvents widen the type III window and reduce both the shear viscosity and the interfacial viscosity, which is the basis for the process called alkaline-co-solvent-polymer (ACP) flooding (Fortenberry et al, 2015). Co-solvents are one tool used to optimize formulations.…”
mentioning
confidence: 99%